Water and energy cycles coupling diagnosed from remotely sensed global observations - abstract - Entekhabi, Dara, author; Colorado State University, publisher (Colorado State University. Libraries, 2016)
Abstract of award lecture "Water and energy cycles coupling diagnosed from remotely sensed global observations" given on March 22, 2016 by Dara Entekhabi, winner of the 2016 Hydrology Days Award.
Hydrology days 2016
AGU hydrology days 2016
2016 annual AGU hydrology days was held at Colorado State University on March 21 - March 23, 2016.
Keywords: Hydrology -- Congresses; Award winners